Exploring complexity in health: an interdisciplinary systems approach : proceedings of MIE2016 at HEC2016 - Hörbst, Alexander; Hackl, Werner; Keizer, Nicolette de; Prokosch, Hans-Ulrich; Hercigonja-Szekeres, Mira; Lusignan, Simon de (Studies in health technology and informatics, 2016)
"The field of health is an increasingly complex and technical one; and an area in which a more multidisciplinary approach would undoubtedly be beneficial in many ways. This book presents papers from the conference "Health--Exploring Complexity: An Interdisciplinary Systems Approach," held in Munich, Germany, from August 28th to September 2nd 2016. This joint conference unites the conferences of the German Association for Medical Informatics, Biometry and Epidemiology (GMDS), the German Society for Epidemiology (DGEpi), the International Epidemiological Association- European Region, and the European Federation for Medical Informatics (EFMI). These societies already have long-standing experience of integrating the disciplines of medical informatics, biometry, epidemiology and health data management. The book contains over 160 papers, and is divided into 14 sections covering subject areas such as: health and clinical information systems; eHealth and telemedicine; big data and advanced analytics; and evidence-based health informatics, evaluation and education, among many others. The book will be of value to all those working in the field of health and interested in finding new ways to enable the collaboration of different scientific disciplines and the establishment of comprehensive methodological approaches"--Publisher's description